2016
DOI: 10.1177/0733464816661947
|View full text |Cite
|
Sign up to set email alerts
|

Resident Aggression and Abuse in Assisted Living

Abstract: This article estimates the prevalence and identifies risk factors of resident aggression and abuse in assisted living facilities. We conducted multivariate analyses of resident-level data from an analytic sample of 6,848 older Americans in the 2010 National Survey of Residential Care Facilities. Nationwide, 7.6% of assisted living residents engaged in physical aggression or abuse toward other residents or staff in the past month, 9.5% of residents had exhibited verbal aggression or abuse, and 2.0% of resident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 33 publications
5
32
0
Order By: Relevance
“…PA, once it has occurred, tends to persist until death . Previous research has shown that residents with dementia (65 years or older), living in assisted living facilities in the United States, have a 5‐fold increase in the likelihood of engaging in physical abuse toward other residents and staff . The demented patient's caregiver is often the victim when it comes to PA .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PA, once it has occurred, tends to persist until death . Previous research has shown that residents with dementia (65 years or older), living in assisted living facilities in the United States, have a 5‐fold increase in the likelihood of engaging in physical abuse toward other residents and staff . The demented patient's caregiver is often the victim when it comes to PA .…”
Section: Introductionmentioning
confidence: 99%
“…10 Previous research has shown that residents with dementia (65 years or older), living in assisted living facilities in the United States, have a 5fold increase in the likelihood of engaging in physical abuse toward other residents and staff. 11 The demented patient 0 s caregiver is often the victim when it comes to PA. 5 A Swiss study showed that 42% of care workers working in nursing homes (where the majority of patients were diagnosed with, or showed symptoms of, dementia) had been physically assaulted at work. 12 To our knowledge, there are no studies comparing prevalence and time at onset of PA among subjects with different neuropathologically confirmed dementias.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with previous research which has identified cognitive impairment as a key factor in aggressive behaviours, particularly in combination with other identified contributors such as acute medical conditions, or long-term psychiatric or personality factors. 7,12,13 The very high degree of cognitive impairment noted among aggressors, and to a lesser extent targets (although the latter is likely to be significantly under-reported), confirms that effective management of the behavioural symptoms associated with dementia and related conditions are a key strategy in preventing RRA. This includes a person-centred approach, which has been defined as incorporating treating people with dementia as individuals and looking at the world from their perspective.…”
Section: Study Limitationsmentioning
confidence: 85%
“…A recent study reported aggressor rates of 7.6% physical aggression, 9.5% verbal aggression and 2.0% sexual aggression per month in assisted living facilities. 7 These included incidents targeted to both staff and residents.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has used different terms to describe residents displaying aggressive behaviours such as "exhibitors" [11,15], "perpetrators" [1,16], "initiators" [2,17], and "aggressors" [10]. Furthermore, prior research has used a variety of terminologies including resident-to-resident abuse [2,[18][19][20], resident-toresident (elder) mistreatment [9,16,[21][22][23][24][25][26], resident-toresident relational aggression [27], resident-to-resident violence [10,17,28], and resident-to-resident (physical) aggression [8,12,13,15,[29][30][31][32]. In 2015, a consensusbuilding workshop with an expert panel of researchers and practitioners reached an agreement on the term resident-to-resident aggression (RRA) defined as: "negative, aggressive and intrusive verbal, physical, sexual, and material interactions between long-term care residents that in a community setting would likely be unwelcome and potentially cause physical or psychological distress or harm to the recipient" [1].…”
Section: Introductionmentioning
confidence: 99%